Valor nutricional de silagens de sorgo colhidas precocemente e reensiladas em diferentes tempos - Vinícius Silveira Raposo (2019)
The aim of two experiments was to evaluate the effect of early harvesting and re-sowing on apparent digestibility and in situ degradability of sorghum silages. In sorghum crops, it may be necessary to harvest early due to bird attacks, as well as to harvest plants with less hard and more digestible grains. Early harvests result in silages with high humidity, which are more prone to losses. Another common practice that predisposes to losses is silage re-location, which has either search for creative solutions to remedy crop failures or been a practice that accompanies the modern trend of specialization of farms in the production of bulky foods. There was no effect (p<0,05) of the sorghum silages relocation harvested early, on nitrogen balance, which show average values of 6.7 g/day. As well as no silage re-location effects of sorghum silages harvested early on the consumption of DM, CP, NDF, FDA, HEM and CEL that presented mean values of 66.0, 4.5, 41.4, 26.6, 16.8, 24.5 g/kg PV0.75, respectively. The effect of silage re-location on the digestibility of sorghum silages harvested early was also not observed (p<0.05). The digestibility of DM, CP, NDF, FDA, HEM and CEL presented mean values of 65.4; 64.8; 65.1; 65.4; 63.7 and 69.2%, respectively. Although for a long time, it was common sense that silage re-location was associated with losses, this hypothesis was not proven in the present work. The same was observed in the in situ test for silage re-relocation. The relocation was not able to alter the ruminal degradation kinetics nor the effective degradability of the organic matter and fibrous fractions of sorghum silage harvested early and reallocated after different exposure times.